2022
DOI: 10.3390/biology11111550
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Trigger Points and Central Sensitization Signs, but No Anxiety, Are Shown in Women with Dysmenorrhea: A Case-Control Study

Abstract: Background primary dysmenorrhea (PD) is considered to be a cyclic chronic pelvic pain, with its onset in menstrual periods, often accompanied by the presence of myofascial trigger points (MTP). Most MTPs in subjects with chronic pelvic pain are in the inferior part of the abdomen, in the rectus abdominis (RA) area. Central sensitization is closely related to chronic pain processes. Previous studies in women with chronic pelvic pain reported central sensitization signs in their subjects, such as lower pain pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The final step involves screening for sensitivity to other stimuli, including sensitivity to sound (phonophobia), light (photophobia), and to the presence of comorbid medical conditions, as well as central nervous system-associated symptoms such as poor sleep quality, fatigue, and cognitive problems [ 14 ]. It is important to emphasize that even though myofascial TrPs can be a primary dysfunction not associated with any medical condition, and would therefore fulfil the nociceptive pain phenotype criteria, they can also be comorbid with other medical conditions associated with central sensitization, such as painful knee osteoarthritis [ 81 ], migraine [ 82 ], cancer, [ 83 ], and dysmenorrhea [ 84 ]. For example, TrP activation due to visceral nociception may persist after appropriate treatment due to nociceptive input from TrPs located in the referred visceral area related to centrally induced visceral hyperalgesia [ 85 ].…”
Section: Clinical Criteria/grading System For Pain Phenotyping Of Myo...mentioning
confidence: 99%
“…The final step involves screening for sensitivity to other stimuli, including sensitivity to sound (phonophobia), light (photophobia), and to the presence of comorbid medical conditions, as well as central nervous system-associated symptoms such as poor sleep quality, fatigue, and cognitive problems [ 14 ]. It is important to emphasize that even though myofascial TrPs can be a primary dysfunction not associated with any medical condition, and would therefore fulfil the nociceptive pain phenotype criteria, they can also be comorbid with other medical conditions associated with central sensitization, such as painful knee osteoarthritis [ 81 ], migraine [ 82 ], cancer, [ 83 ], and dysmenorrhea [ 84 ]. For example, TrP activation due to visceral nociception may persist after appropriate treatment due to nociceptive input from TrPs located in the referred visceral area related to centrally induced visceral hyperalgesia [ 85 ].…”
Section: Clinical Criteria/grading System For Pain Phenotyping Of Myo...mentioning
confidence: 99%
“…In chronic lower back pain, high trait anxiety-related personality characteristics predict the extent of CS symptoms [16]. However, some studies have found negative relationships between CS and depression and anxiety [17][18][19]. The relationship between CS and depression and anxiety has been inconsistent in previous studies, and the study population has been limited to specific pain-related diseases.…”
Section: Introductionmentioning
confidence: 99%